Use of ChatBots in Programming Education: A Scoping Review - Alves, João Victor Barroso; Gonçalves, Yanna Torres; Silva, Henrique Barbosa (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
Proficiency in programming languages is essential across various sectors. As technology advances, AI-driven chatbots are increasingly recognized for their potential in education. This paper presents a scoping review of chatbots in programming education, examining existing research to identify benefits, challenges, and user perceptions. Findings reveal positive impacts on learning and widespread student adoption. However, gaps exist, such as limited focus on teachers' perspectives and issues with student engagement and accessibility.